2008
DOI: 10.1002/jor.20576
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in passive knee biomechanical properties in tibial rotation

Abstract: The anterior cruciate ligament (ACL) is the most commonly injured knee ligament with the highest incidence of injury in female athletes who participate in pivoting sports. Noncontact ACL injuries commonly occur with both internal and external tibial rotation. ACL impingement against the lateral wall of the intercondylar notch during tibial external rotation and abduction has been proposed as an injury mechanism, but few studies have evaluated in vivo gender-specific differences in laxity and stiffness in exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
2
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 48 publications
(115 reference statements)
3
71
2
3
Order By: Relevance
“…As for rotational knee laxity, it has been shown that women have up to 40 % higher knee rotation compared to men [32]. This difference has been confirmed by several investigations [18,32,36,55].…”
Section: Influencing Factorsmentioning
confidence: 64%
See 1 more Smart Citation
“…As for rotational knee laxity, it has been shown that women have up to 40 % higher knee rotation compared to men [32]. This difference has been confirmed by several investigations [18,32,36,55].…”
Section: Influencing Factorsmentioning
confidence: 64%
“…The average side-to-side difference (SSD) between normal knees was 3.5° [31]. -Device by Park et al [32]: Park et al [32] presented the first motorized device to measure knee rotational laxity. The patient sits in a modified chair with the hips flexed at 85°and knees at 60°.…”
Section: Static Rotational Knee Laxitymentioning
confidence: 99%
“…There is a paucity of published information concerning the relationship between knee hyperextension and stress concentration on the reconstructed ACL. However, it is possible, in patients with knee hyperextension, a reconstructed ACL may undergo more consistent severe stress than in those with normal knee laxity because of the absence of sufficiently taut ligaments and tendons that surround the lower extremity, stabilize the knee, and absorb ground reaction force [18,21]. Actually, hyperextension of the knee and physiologic joint laxity have been considered intrinsic factors contributing to traumatic ACL injuries [23,25].…”
Section: Discussionmentioning
confidence: 99%
“…Another study (Park et al 2008) compared ten healthy men and ten healthy women with the knee at 60 of flexion and established that women had increased external rotation laxity. Branch et al (2010a) also reported gender-related outcomes with implications on detection of risk factors for ACL injury.…”
Section: Robotic Systemsmentioning
confidence: 98%
“…Robotic systems have promised to overcome bias inherent to manual force application by means of comprising mechanical methods to apply load or torque in a controlled mode (magnitude, direction, rate) (Lob et al 2006;Park et al 2008;Tsai et al 2008;Robert et al 2009;Woo and Fisher 2009;Branch et al 2010a;Musahl et al 2010;Citak et al 2011;Mayr et al 2011). …”
Section: Robotic Systemsmentioning
confidence: 98%